2015
DOI: 10.6113/jpe.2015.15.3.849
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Type Hybrid Energy Storage System and Its Mode Control Strategy for Electric Vehicles

Abstract: This paper proposes a novel compound-type hybrid energy storage system (HESS) that inherits the unique advantages of both battery/supercapacitor (SC) and the SC/battery HESSs for electric vehicles (EVs). Eight operation modes are designed to match this system. A mode control strategy is developed for this HESS on the basis of these modes, and five classes of operation modes are established to simplify this strategy. The mode control strategy focuses on high operating efficiency and high power output. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Based on the above reasons, it can be concluded that the state of charge trajectories of the battery and supercapacitor can directly affect the final control effect of the predicted-energy control system [33][34][35]. Therefore, the charging states of the lithium battery and supercapacitor can be elected as the state Figure 3: Supercapacitor model equivalent circuit variables of the system.…”
Section: Energy-predictive Control Strategy Based On a Markov Modelmentioning
confidence: 99%
“…Based on the above reasons, it can be concluded that the state of charge trajectories of the battery and supercapacitor can directly affect the final control effect of the predicted-energy control system [33][34][35]. Therefore, the charging states of the lithium battery and supercapacitor can be elected as the state Figure 3: Supercapacitor model equivalent circuit variables of the system.…”
Section: Energy-predictive Control Strategy Based On a Markov Modelmentioning
confidence: 99%
“…HESS's research involves topology design, battery modeling, supercapacitor modeling and SOC estimation, SOH prediction, DC-DC converter control strategies, power distribution strategies, and system stability analysis [ 2 5 ]. We conducted in-depth research on the power management system for electric vehicles, and then proposed a simplified cascading HESS topology configuration with the adaptive sliding mode control algorithm [ 6 8 ]. Our research has been applied to SUDA brand electric car successfully.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned energy storage hybridization concept has shown clear benefits in the transportation sector [23] and has resulted in numerous successful EV applications [9,10,[24][25][26]. A parallel battery/ultracapacitor HESS topology with independent load control of individual energy storages should be well suited for energy management control tasks [6,7,11,26,27].…”
Section: Introductionmentioning
confidence: 99%